Current treatment of infected non-union after intramedullary nailing. (June 2017) - Simpson, A. Hamish; Tsang, Jerry S.T
Abstract: Non-union is a devastating consequence of a fracture. Non-unions cause substantial patient morbidity with patients suffering from loss of function of the affected extremity, increased pain, and a substantial decrease in the quality of life. The management is often associated with repeated, unsuccessful operations resulting in prolonged hospital stays, which has social and economic consequences to both the patient and the healthcare system. The rates of non-union following intramedullary (IM) nailing vary according to anatomical location. There is currently no consensus regarding the treatment of infected non-unions following IM nailing, but the most common procedures reported are; exchange IM nail with antibiotic suppression or excision of the non-union, (stabilisation with external fixation or less commonly plate or IM nail) and then reconstruction of the bone defect with distraction osteogenesis or the Masquelet technique. This article explores the general principles of treatment, fixation modalities and proposes a treatment strategy for the management of infected non-unions following intramedullary nailing.